Techno-economic analysis of solar PV power-to-heat-to-power storage and trigeneration in the residential sector. (15th December 2019) - Datas, A.; Ramos, A.; del Cañizo, C.
Highlights: Techno-economic assessment of residential power-to-heat-to-power storage. The integration with a solar PV system in a dwelling in Madrid is considered. Electricity savings beyond 70% and payback periods lower than15 years are possible. Payback periods lower than 10 years are possible when using an absorption chiller. Additional fuel savings of 20% are possible due to the consumption of exhaust heat. Abstract: This article assesses whether it is profitable to store solar PV electricity in the form of heat and convert it back to electricity on demand. The impact of a number of technical and economic parameters on the profitability of a self-consumption residential system located in Madrid is assessed. The proposed solution comprises two kinds of heat stores: a low- or medium-grade heat store for domestic hot water and space heating, and a high-grade heat store for combined heat and power generation. Two cases are considered where the energy that is wasted during the conversion of heat into electricity is employed to satisfy either the heating demand, or both heating and cooling demands by using a thermally-driven heat pump. We compare these solutions against a reference case that relies on the consumption of grid electricity and natural gas and uses an electrically-driven heat pump for cooling. The results show that, under relatively favourable conditions, the proposed solution that uses an electrically-driven heat pump could provide electricity savings in the range of 70 – 90% with a payback period of 12 – 15 years, plus an additional 10 – 20% reduction in the fuel consumption. Shorter payback periods, lower than 10 years, could be attained by using a highly efficient thermally driven heat pump, at the expense of increasing the fuel consumption and the greenhouse gas emissions. Hybridising this solution with solar thermal heating could enable significant savings on the global emissions, whilst keeping a high amount of savings in grid electricity (>70%) and a reasonably short payback period (<12 years).